2015
DOI: 10.1245/s10434-015-4688-8
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Perceptions of Surgical Oncology Fellows on ACGME Accreditation and the Complex General Surgical Oncology Certification

Abstract: The majority of the surveyed surgical oncology fellows and candidates believe that obtaining board certification in CGSO is important and will help them pursue their career goals. However, the decision to specialize in surgical oncology does not appear to be motivated by ACGME accreditation or the new board certification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…A 2015 survey conducted of CGSO fellows and fellowship applicants, reported that 80% of respondents stated that the decision to pursue a CGSO fellowship was not influenced by ACGME accreditation 8 . Despite this, 73% of fellows and 94% of fellowship applicants felt that board certification would be helpful in attaining their career goals.…”
Section: Introductionmentioning
confidence: 99%
“…A 2015 survey conducted of CGSO fellows and fellowship applicants, reported that 80% of respondents stated that the decision to pursue a CGSO fellowship was not influenced by ACGME accreditation 8 . Despite this, 73% of fellows and 94% of fellowship applicants felt that board certification would be helpful in attaining their career goals.…”
Section: Introductionmentioning
confidence: 99%
“…This finding has not been emphasized in other literature but it does indicate a key perspective and role for program leadership in this regard. Although residents in other fields have expressed that their certification exams were important to them, difficulty in motivation to study during residency has not been reported [16]. Our residents reported factors such as fatigue and lack of time to prepare as contributing factors, which is not surprising given the rigor of residency training.…”
Section: Discussionmentioning
confidence: 57%
“…The general desire is that such accreditation will serve to enhance surgical care delivered to cancer patients. 8,9 This may also serve to centralize cancer care among high volume institutions, where volume has been an independent surrogate marker of surgical outcome that contributes to differences in survival. 1012 The board certification process in surgical oncology is still in its early phases, and the true value of board certification in surgical oncology remains to be objectively determined.…”
Section: Comparing the Us And Uk Health Systemsmentioning
confidence: 99%